Progress and Perspective of Constructing Solid Electrolyte Interphase on Stable Lithium Metal Anode - Yu, Jing; Zhao, Liang; Huang, Yanfei; Hu, Yi; Chen, Likun; He, Yan-Bing (Frontiers in Materials, 2020)
Lithium metal is considered as one of the most promising anode materials for high-energy-density rechargeable batteries. However, uncontrolled dendrite growth, the unstable interface between lithium metal anode and electrolyte, and infinite volume change are major obstacles in their practical applications. Constructing a solid electrolyte interphase (SEI) with high strength, good stability and desirable flexibility is one of the most promising approaches to mitigate the volume expansion of lithium anode and induce the uniform deposition of lithium for dendrite-free anode. Herein, we summarize the advances of SEI modification from the aspects of in-situ (adding electrolyte additives) and ex-situ (constructing artificial SEI) methods. The ideal SEI on lithium anode can effectively suppress the lithium dendrite growth and volume change of lithium metal anode. In the future study, the modification of SEI should focus on the suppression of side reactions between active lithium metal and electrolyte and the formation of dead lithium, which is quite significant to reduce the consumption of active lithium anode and electrolyte for safe and long-life high energy lithium metal batteries. Constructing an excellent SEI is a robust strategy to achieve the highly stable lithium metal anode for practical application of lithium metal batteries.